Development of a Sustainable Economic Empowerment Model Through Islamic Micro Finance: Evidence of Intellectual Treasure of Pesantren in Indonesia - Retnowati, May Shinta; Ahid, Nur; Rahman, Zayad Abd.; Al Faruqi , Musta'an (AL-IKTISAB: Journal of Islamic Economic Law, 2025)
This research aims to design an appropriate economic empowerment model for Islamic Micro Finance Institutions (IMFI), especially Baitul Maal wat Tamwil (BMT) in Indonesia which is an intellectual treasure of pesantren in Indonesia such as Gontor. The purpose of this research is a critical review the sustainable economic empowerment model of pesantren from the IMFI Gontor pesantren. This research used qualitative method. It conducts in-depth interviews with experts and practitioners, while to collect secondary data from relevant sources and analysis through qualitative and descriptive. The validity of the data is examined through triangulation and extension from consumers. The data obtained through interviews is then analyzed qualitatively, with several stages, data preparation, categorizing data, describing data, analyzing information, and demonstrating its core ideas and supporting data using discussions, tables, pictures, and narratives. The results is, BMT La Tansa is a IMFI under the auspices of Pondok Modern Darussalam Gontor (PMDG). This project is carried out with a mudharabah contract, which is supervised by the pesantren and BMT. This research is based on the Indonesian context because it is influenced by the typical conditions of the country. Even so, some of the findings in this rsearch can be evidence as a model of economic development which is a form of pesantren treasure. The proposed model can be a contribution of pesantren on IMFI to be able to improve the quality of life for the pesantren community and the surrounding community in sustainable economic empowerment through business capital. This research focuses on intellectual treasure to create a sustainable business model in accordance with sharia principles.